Cork oak woodlands on the edge : (Island Press, 2009)
Cork oak has historically been an important species in the western Mediterranean—ecologically as a canopy or “framework” tree in natural woodlands, and culturally as an economically valuable resource that underpins local economies. Both the natural woodlands and the derived cultural systems are experiencing rapid change, and whether or not they are resilient enough to adapt to that change is an open question. Cork Oak Woodlands on the Edge provides a synthesis of the most up-to-date, scientific, and practical information on the management of cork oak woodlands and the cultural systems that depend on cork oak. In addition, Cork Oak Woodlands on the Edge offers ten site profiles written by local experts that present an in-depth vision of cork oak woodlands across a range of biophysical, historical, and cultural contexts, with sixteen pages of full-color photos that illustrate the tree, agro-silvopastoral systems, products, resident biodiversity, and more. Cork Oak Woodlands on the Edge is an important book for anyone interested in the future of cork oak woodlands, or in the management of cultural landscapes and their associated land-use systems. In a changing world full of risks and surprises, it represents an excellent example of a multidisciplinary and holistic approach to studying, managing, and restoring an ecosystem, and will serve as a guide for other studies of this kind.